Multiply (2x+4)^2
Whenever you have something of the form (a + b)^2 you wanna apply the identity:
(a + b)^2 = a^2 + 2*a*b + b^2 thus:
(2x + 4)^2 = 4x^2 + 16x + 16
Multiply (2x+4)^2
Whenever you have something of the form (a + b)^2 you wanna apply the identity:
(a + b)^2 = a^2 + 2*a*b + b^2 thus:
(2x + 4)^2 = 4x^2 + 16x + 16
Hey there. Since you are squaring it, you multiply it by itself. Thus it's:
(2x + 4)(2x + 4)
You need to FOIL it. You know, First, Outside, Inside, Last:
4x^{2} + 8x + 8x + 16.
Then combine like terms:
4x^{2} + 16x + 16.
Shake a leg.